2023
DOI: 10.1177/03795721231179786
|View full text |Cite
|
Sign up to set email alerts
|

Advancing a Multisectoral Platform for Nutrition-Sensitive Agriculture in Nigeria: Reflections on Effectiveness and Lessons Learned

Abstract: Background: Inadequate coordination mechanisms and capacity to coordinate are limiting factors for maximizing the ability of agriculture to improve nutrition in Sub-Saharan Africa. Effective coordination requires the availability of a platform for stakeholder convening, planning, operationalization of ideas, communication, and accountability. Nigeria’s Federal Ministry of Agriculture and Rural Development established one such platform to support the institutionalization of nutrition-sensitive agriculture. Plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The already mentioned IANWG was established as the primary coordination mechanism for NSA within FMARD and between FMARD and other ministries, departments, and agencies (MDAs) for the purposes of policy coherence, consistency, and synergy. In the Special Issue, Adeyemi et al 23 highlight the various coordination mechanisms that exist for different purposes, while Ezekannagha et al 39 describe the IANWG and its challenges and prospects. Overall, the FMARD needs to continue to actively participate in national coordination structures such as the National Committee on Food and Nutrition and the National Council on Nutrition.…”
Section: Multisectoral Coordinationmentioning
confidence: 99%
See 2 more Smart Citations
“…The already mentioned IANWG was established as the primary coordination mechanism for NSA within FMARD and between FMARD and other ministries, departments, and agencies (MDAs) for the purposes of policy coherence, consistency, and synergy. In the Special Issue, Adeyemi et al 23 highlight the various coordination mechanisms that exist for different purposes, while Ezekannagha et al 39 describe the IANWG and its challenges and prospects. Overall, the FMARD needs to continue to actively participate in national coordination structures such as the National Committee on Food and Nutrition and the National Council on Nutrition.…”
Section: Multisectoral Coordinationmentioning
confidence: 99%
“…23 Yet, the IANWG experienced multiple long periods of inactiveness despite efforts to keep it operational. Hence, a study, which is reported in this special issue, 39 was conducted in 2018 to identify approaches for sustaining the activities of the IANWG.…”
Section: Narratives Knowledge and Evidencementioning
confidence: 99%
See 1 more Smart Citation